Expansionary Monetary Policy vs. Bank Concentration: The Eurozone & Other European Countries - Jović, Željko (Panoeconomicus, 2025)
Expansionary monetary policy combined with unconventional measures led to a decline in the profitability of U.S. and European banks. This paper studies whether such measures also affect the asset concentration in the European banking sector. The findings of this research add value to previous research, taking a step deeper into examining the consequences of expansionary monetary policy. It is found that reductions in the European central bank’s (ECB’s) key policy rate can predominantly explain the concentration growth in the eurozone countries. Furthermore, the ECB’s monetary policy had a more substantial influence on the growth of the concentration of banks outside the eurozone than those countries’ own monetary policies. Thus, the expansionary monetary policy poses specific challenges to financial stability in Europe. JEL: E44, E52, E58, G21